1998
DOI: 10.1046/j.1432-1327.1998.2580540.x
|View full text |Cite
|
Sign up to set email alerts
|

The deoxyribonuclease activity attributed to ribosome‐inactivating proteins is due to contamination

Abstract: The mode of action of ribosome-inactivating proteins (RIPs) has, for many years, been considered to be depurination of a specific adenyl residue of ribosomal RNA, resulting in inhibition of protein synthesis. Recently, this view has been challenged by the observation that many RIP preparations have significant DNase activity in addition to their N-glycosidase activity. In this study, we have investigated the putative DNase activity of two RIPs, ricin and pokeweed antiviral protein (PAP), and show that, in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…Nonetheless, RNase A caused degradation of the substrate, RNA GdAGA. Although ricin A chain has been reported to be unaffected by diethylpyrocarbonate [22], we observed inhibition of ricin (not shown) that limited the usable DEPC concentration such that treatment with this chemical rendered only a slight mitigation of the interference by RNase A (Table 4). Since RNases are known to be present in castor bean extracts [24] and perhaps in illicit weapons made therefrom, we investigated whether a polyclonal antiricin antibody linked to Dynabeads might be useful in removing ricin from potential interferences in solution.…”
Section: '-Rumentioning
confidence: 62%
See 1 more Smart Citation
“…Nonetheless, RNase A caused degradation of the substrate, RNA GdAGA. Although ricin A chain has been reported to be unaffected by diethylpyrocarbonate [22], we observed inhibition of ricin (not shown) that limited the usable DEPC concentration such that treatment with this chemical rendered only a slight mitigation of the interference by RNase A (Table 4). Since RNases are known to be present in castor bean extracts [24] and perhaps in illicit weapons made therefrom, we investigated whether a polyclonal antiricin antibody linked to Dynabeads might be useful in removing ricin from potential interferences in solution.…”
Section: '-Rumentioning
confidence: 62%
“…DNases reportedly contaminate many preparations of RIPs, but DNase I had no effect on the assay (Table 4) [22]. The chelating agent EDTA was included in the toxin reaction (2 mM) and in the stop/detection reagents (0.7 mM) to avoid degradation of oligonucleotides due to Signal-to-Background Ratio Ricin (ng/ml in 5 μl sample) Fig.…”
Section: '-Rumentioning
confidence: 99%
“…PAP was heat treated to remove the non-specific glycosidase/nuclease activity while retaining the RNA N-glycosidase activity (49). Adenine release was detected on incubating A-14 with a commercial source wild type PAP at pH 7.8 (25 mM Tris/HCl buffer).…”
Section: Kinetics Of A-14 Turnover By Pokeweed Antiviral Protein (Pap)mentioning
confidence: 99%
“…19 The presumed novel enzymatic activities have been challenged, since concerns were formulated about contaminating nucleases in the RIP preparations. 20 However, various papers have shown that DNA cleavage activity is observed even for highly pure RIPs 7,[21][22][23][24][25][26][27] and that reduction in N-b-glycosidase activity results in a reduction of DNA cleaving activity, 21 reinforcing the concept that RIPs use the same catalytic site for their two-fold activity. 28 Leaves of Phytolacca dioica express four type 1 RIPs, named PD-L1, PD-L2, PDL3, and PD-L4.…”
mentioning
confidence: 99%